ナンキョク ノ クラゲ ルイ - 内田, 亨; ウチダ, トオル; UCHIDA, Tohru (国立極地研究所, 1971)
P(論文) 南極から4種の水母を報告した.1種は新種で1種は南極付近の固有種,他の2種は幼形のため種の同定はできなかった. The present paper describes four medusae from the Antarctic, including a new species of Rathkea, the genus hitherto only known in the Northern Hemispere. departmental bulletin paper